Left diaphragmatic rupture in vehicle trauma: Report of surgical treatment and complications of two consecutive cases - Conti, Luigi; Grassi, Carmine; Delfanti, Rocco; Cattaneo, Gaetano Maria; Banchini, Filippo; Capelli, Patrizio (Acta Biomedica Atenei Parmensis, 2021)
Background and aims:Diaphragmatic ruptures are associated with blunt abdominal or thoracic trauma and often occur in car and motorbike accident with a high energy impact. Case presentation: We report two cases of patients victims of car and motorbike accidents that were referred to the Emergency Department of our Hospital in August and September 2017 for a politrauma. The patients were both diagnosed with a left diaphragmatic rupture with herniation of the stomach in the chest, and decomposed fractures of the ribs. One of the two patients reported a large abdominal wound with loss of substance in the site of the impact. Both patients underwent to open emergency surgery with primary repair of the phrenic rupture. The post-operative course was characterized by the occurrence of complications such as respiratory distress and emothorax for one of the patients. Conclusion: Traumatic rupture of the diaphragm can be associated to blunt or penetrating abdominal trauma in car and motorbike accident with a prevalence of the left-sided lesions. In patients with politrauma an associate rupture of the diaphragm should be always suspected especially in motor accident where high energy impact can generate a traumatic laceration of the respiratory muscle. The treatment of associate thoracic wall fractures to prevent weaning and respiratory distress in intubated patient should be discussed.